Changes in temperature preferences and energy homeostasis in dystroglycan mutants. - Takeuchi, K.; Nakano, Y.; Kato, U.; Kaneda, M.; Aizu, M.; Awano, W.; Yonemura, S.; Kiyonaka, S.; Mori, Y.; Yamamoto, D.; Umeda, M. (Science, 2009)
Temperature affects the physiology, behavior, and evolution of organisms. We conducted mutagenesis and screens for mutants with altered temperature preference in Drosophila melanogaster and identified a cryophilic (cold-seeking) mutant, named atsugari (atu). Reduced expression of the Drosophila ortholog of dystroglycan (DmDG) induced tolerance to cold as well as preference for the low temperature. A sustained increase in mitochondrial oxidative metabolism caused by the reduced expression of DmDG accounted for the cryophilic phenotype of the atu mutant. Although most ectothermic animals do not use metabolically produced heat to regulate body temperature, our results indicate that their thermoregulatory behavior is closely linked to rates of mitochondrial oxidative metabolism and that a mutation in a single gene can induce a sustained change in energy homeostasis and the thermal responses.